Religious Moderation of Generation Z: Attitude of Students’ Religious Tolerance in Strengthening the Character of the Nation - Rusli, Rusdi; Ainah, Noor; Arief, Muhammad Ihsanul; Husin, Gusti Muhammad Irhamna (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The complex Indonesian society requires the residents to always maintain good relations to realize a harmonious life with each other. Peaceful and conflict are the potential two poles presenting in human life. Maintaining stable community conditions is a shared responsibility, from the government to the small community level. Besides, the level of the role of academics, especially students, becomes important as an object of research. Religious moderation is a wise attitude toward one's self during the conditions of a multicultural and multireligious society. Researchers focus on how the attitude of religious moderation in the form of tolerance of students representing generation Z, Universitas Lambung Mangkurat Banjarmasin, can be questioned. The students who are the object of their research are studying at FKIP, FK, and FEB. The results of research findings based on a standard of tolerance indicators that correspond to students’ response are more likely to be in an attitude of mutual respect, mutual help among each other, focus on equality, and always tolerance for all communities. In addition, the researchers classified the research findings based on the response of the answers on three categories of students: pluralist, inclusive, and exclusive. Potential attitudes tend to make students enter the pluralist category up to 53%. The type thus shows that students are more receptive to differences by supporting each other's good in the teachings of religions. Next, there are 41% enter the inclusive category. This category tends students to welcome differences in beliefs, but they still hold more of what is within the religions. The last category is exclusive, with 6% of the student classification results. This third catalog fully believes that goodness and truth are only in the person of his religion. Therefore, the three classifications' results show that Lambung Mangkurat University students tend to be more open to each other in the difference of beliefs. It will give positively impact on collaborative affairs in solving specific problems that need to be solved together, especially regarding the issues of this nation.